"Strategie control? - A five factor model" - Tavakoli, Iraj; Perks, Keith (Marketing & Menedzsment, 2019)
The area of strategic control is one that is replete with a confusing array of recipes, prescriptions and frameworks. This paper analyses and clarifies the various strands of literature culminating in a comprehensive strategic control framework. Strategic control is part of the evolution of concepts and thinking in the history of management control, which is no longer the sole pre-occupation of financial and management accountants. Control systems have moved on from the retrospective financial control approach to the development of feed forward, future oriented control systems tracking long term strategic goals and objectives. The paper proposes a five-factor model to ensure that major shifts in a single firm or business unit's environment are monitored and controlled and discusses the implications for managers. A central aim is to provide managers with a practical conceptual framework for strategic control which embraces contemporary developments in the area. The paper does not discuss some of the other important aspects of strategic control, such as the methods, systems and structures for good strategic control.